Snacking, satiety, and weight: A randomized, controlled trial - Njike, Valentine Yanchou; Kavak, Yasemin; Treu, Judith A.; Doughty, Kimberly; Katz, David L. (American Journal of Health Promotion, 2017)
Purpose. To compare the effects of nut-based snack bars (NBSB) vs. prepackaged 200-kcal portions of typical conventional snack foods, when consumed over a 12-week period by a group of overweight adults. Design. Randomized, single-blind parallel design with two treatment groups. Setting. Clinical trial. Subjects. Thirty-four overweight participants were enrolled. Intervention. Commercially available NBSB or conventional snack foods as part of an ad libitum diet for 12 weeks. Measures. Primary outcome measures: body mass index, body weight, body composition, waist circumference. Secondary outcome measures: blood pressure, lipid profile, nutrients intake, hunger/satiety, quality of life. Analysis. Generalized linear models with time as repeated measure were used to analyze these data. Results. Daily consumption of NBSB for 12 weeks, as compared to daily consumption of conventional snacks, significantly reduced percentage body fat (-1.7% +/- 10.8% vs. 6.2% 6 9.3%; p = .04) and visceral fat (-1.3 +/- 5.9 vs. 2.7 +/- 4.0; p = .03). There were no between-group differences (p ¿ .05) for blood pressure, lipid panel, satiety, or quality of life measures. Conclusion. Our data suggest that daily consumption of NBSB for 12 weeks reduced body fat and had no adverse effects on weight, blood pressure, lipid profile, satiety, or quality of life in this small sample of overweight adults.
Keywords: Adult; Aged; Blood Pressure; Body Mass Index; Body Weight; Body Weights and Measures; Diet; Energy Intake; Female; Health focus: hunger/satiety, nutrition, quality of life; Humans; Male; Middle Aged; Nuts; Outcome measure: body mass index, body weight, body composition, waist circumference, blood pressure, lipid profile, nutrients intake, hunger/satiety, quality of life; Overweight; Quality of Life; Research purpose: intervention testing; Satiation; Setting: clinical; Single-Blind Method; Snacking, Satiety, Overweight, Prevention Research. Manuscript format: research; Snacks; Strategy: education, incentive; Study design: randomized, single-blind parallel trial; Target population age: overweight adults; Target population circumstances: geographic location; adult; aged; blood pressure; body mass; body weight; caloric intake; controlled study; dept.pch; diet; diet therapy; fast food; female; human; male; middle aged; morphometry; nut; obesity; peer-reviewed; quality of life; randomized controlled trial; satiety; single blind procedure